The Relationship Between Fluid Intake and Heat Sress with the Hydration Status of Workers: A Scooping Review - Pramesti, Shinta Dwi Surya; Denny, Hanifa M.; Setyaningsih, Yuliani (Indonesian Journal of Global Health Research, 2024)
The importance of adequate water consumption as a key factor in preventing dehydration in workers is a crucial aspect in the work environment. The body, which loses fluids through sweat, urine, and respiration, needs adequate fluid replacement to prevent dehydration. Heat stress can accelerate the dehydration process, where the body responds by producing sweat to regulate body temperature. Objective: The aim of this study is to investigate the relationship between fluid intake, heat stress, and the hydration status of workers. Method: The method used in this article review is PRISMA-ScR. The publication language is English. The search was conducted through several scientific journal databases, including Scopus, Science Direct, PubMed, SpringerLink, EBSCO Host, and ProQuest, covering the period from 2013 to 2023. The process of selecting evidence sources in the initial identification yielded 21,403 articles, then through a selection process based on eligibility, topic relevance, and final assessment, eight evidence sources were selected through five stages of selection. Eligible and selected data sources are presented in a charting table. Results: The findings of this scoping review reveal that there is a connection between fluid intake, heat stress, and the hydration status of workers. The article highlights a strong correlation between fluid intake, heat stress, and hydration status in workers, emphasizing the importance of maintaining hydration balance. Conclusions: The findings suggest that while fluid intake is crucial, heat exposure can elevate the risk of dehydration, especially in hot indoor or outdoor environments.